GRANULITISATION OF FRONTAL NAPPES IN THE KABYÈ MASSIF IN NORTHERN TOGO - B. E., Sabi; M. D.-T., Gnazou; M. S., Taïrou; K. A., Togbe; A. K. C., Johnson (European Scientific Journal, ESJ, 2015)
The Kabyè Massif represents one of disseminated hills which marks the suture zone of the Panafrican Dahomeyides Belt in northen Togo. Coronitic structures were described in high-grade granulites composing the frontal nappes on the south-western edge of the massif. Granulitisation is investigated through petrofabric study of the frontal nappes rocks of Kabyè Massif. Two stages of granulitisation are revealed: the first one corresponds to the formation of granulites with an Opx + Pl + Cpx + Grt ± Qtz paragenesis ; the second one has a Cpx + Pl + Grt + Qtz ± Ilm mineral assemblage. The former corresponds to metamorphic recristallization of about medium-pressure to high-temperature conditions (P = 10 to 13 kbar and T = 900 with 1000°C). The latter, which developed coronitic structures, is interpretated as formed at an ultra-high-pressure and medium- to hightemperature conditions (P = 13 to 19 kbar and T = 850 to 900°C). These coronitic petro-fabrics define an anticlockwise P-T paths trajectories corresponding to the collision and the beginning of the nappes extraction during the Panafrican tectonics.